Depression among adolescents: a review of beck’s cognitive behaviour theory - Fauziah Zaiden,; Mastura Mahfar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The phenomenon of depression has been a major concern recently, both nationally and globally. Depression is a disorder that involves changes in thoughts, emotions, feelings, and behaviours that make a person’s daily life difficult, and if left untreated, can adversely affect individuals and society. Depression among adolescents certainly deserves attention as this group is considered as an asset that will drive the country in the future. In terms of methodology, PubMed, Science direct, and Google Scholar search engines were used which focused on psychological theories related to adolescent depression. In addition, the search also focuses on Cognitive Approach or more precisely, about Cognitive Behaviour Theory (CBT). Over the past few decades, Cognitive Behaviour Theory (CBT) has been proven to be the most dominant theory in psychological studies including depression in adolescents. As a result, it is found that, under the CBT group, Learned Helplessness Theory and Beck’s Cognitive Behaviour Theory were the two most widely discussed on the concept of depression to date. Therefore, this article will discuss the background and the concept of these theories in describing depression. However, Beck’s CBT has been selected as the most appropriate theory in discussing depression in adolescents because this theory is able to explain this issue further and in detail, in addition to having an extensive amount of research showing the effectiveness of Beck’s CBT in helping adolescents with depression compared to Learned Helplessness Theory.